Diversity and density of crabs in degraded mangrove area at Tanjung Panjang Nature Reserve in Gorontalo, Indonesia - NURAIN LAPOLO; RAMLI UTINA; DEWI WAHYUNI K. BADERAN (Society for Indonesian Biodiversity, 2018)
Lapolo N, Utina R, Baderan DWK. 2018. Diversity and density of crabs in degraded mangrove area at Tanjung Panjang Nature Reserve in Gorontalo, Indonesia. Biodiversitas 19: 1154-1159. This study was aimed to analyze the diversity and the density of crabs in a degraded mangrove area including in the intact mangrove area and the fishponds (the degraded mangrove area).. The data from this study could be used as supporting data for decision makers to slow down the degradation of mangrove along the area of Tanjung Panjang Natural Reserve. The observed data i.e diversity and density of crabs were collected using the stratified random sampling method (10 m x 10 m plot). Environmental parameters suited to crab habitat were also measured. The samples were taken from 18 spots. The study shows that 20 species of crabs were obtained within the mangrove area, and 11 species were founded within the fishponds area. Interestingly, two species of crabs i.e Varuna yui and Varuna litterata were only founded in fishponds area. The density of crabs in mangrove area ranged between 3.23 ind/300m2 and 4.52 ind/300m2, while the density of crabs in fishponds area ranged between 0.16 ind/300m2 and 0.63 ind/300m2. Further study revealed that characteristics and the age of mangrove trees affected macrozoobenthic biota (Gastropods, Bivalvia, Mud Lobster, Polychaeta, and shrimp) as well as fish diversity within mangrove in Tanjung Panjang Natural Reserve. These may be important for further restoration program of mangrove ecosystem and the sustainable restocking for conservation purposes.